Central African Economic and Monetary Community (CEMAC) : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on the Central African Economic and Monetary Community (CEMAC) reviews the evolution of actual and equilibrium real effective exchange rates (REER). The current level of the CEMAC REER is broadly in line with its long-term equilibrium value. The estimation approach herein is subject to certain limitations, some of which are inherent to the literature that tries to estimate the equilibrium REERs. Absolute statements about magnitudes of any possible misalignments should be avoided given the degree of model uncertainty; error bands around estimated equilibrium exchange rates may, in some cases, yield inconclusive results.